Effect of curry leaf and clove bud essential oils on textural and oxidative stability of chill stored sutchi catfish fillets. Issue 3 (5th December 2016) - Binsi, P. K.; Ninan, George; Ravishankar, C. N.
Abstract: Effect of coating with curry leaf and clove essential oils (EO) on oxidative and textural stability of sutchi catfish fillets were evaluated during chilled storage. The changes in parameters associated with textural and lipid degradation was also evaluated to ascertain the interactive effect of polyphenols with muscle proteins. Further, the results were compared against vacuum and conventional polyethylene packaging practices. Prior to coating, the properties of antioxidants were evaluated in vitro based on total phenolic and flavonoid contents, 2, 2‐diphenyl‐1‐ picrylhydrazyl radical scavenging activity, inhibition of linoleic acid peroxidation, iron reducing power, and metal chelating ability. Coating with clove bud EO was found to be more effective in protecting the textural quality and retarding lipid oxidation of the fillets during chilled storage. Curry leaf EO was found to have only moderate effect. Practical applications: In addition to the well‐studied antibacterial and antioxidant properties, plant polyphenols have become an intense focus of research for their ability to cross‐link proteins that widens their applications for textural and functional modification of food and beverages. Currently, a number of carcinogenic chemicals such as ammonia and formalin are hazardously used to prevent texture deterioration in chilled fish associated with post‐rigor changes and microbial reactions. This study evaluates the efficacy of polyphenols present in culinary herbs such as clove bud and curry leaf EO, in stabilising the texture of fish meat during chilled storage. From the results, it could be inferred that both the EO at 0.25% level mediated protein cross‐linking/complexation and maintained textural integrity during chilled storage apart from exhibiting antioxidant activities.